Language Development in Early Childhood: Quality of Teacher-Child Interaction and Children’s Receptive Vocabulary Competency - Yang, Ning; Shi, Jiuqian; Lu, Jinjin; Huang, Yi (Frontiers in Psychology, 2021)
High-quality teacher-child interactions in early learning environments have been regarded as a key contributor to children’s early language and cognitive development in international scholarships. Little is known, however, about the longitudinal effects of children’s receptive vocabularies in the Chinese context. In this study, we addressed the question of such longitudinal effects by examining the predictive effect of preschool teacher-child interaction quality on children’s subsequent receptive vocabulary development in 42 kindergartens in Guangdong Province China. The results in a nested design showed that except for the factor of Emotional Support, the other two factors (Classroom Management, and Instructional Support) were positive predictors to children’s vocabulary competency from K2 (T1) to K3 (T2) at preschools. Findings contribute to the growing international literature on the critical role teacher-child interaction quality plays in children’s language and literacy learning and development. Implications for enhancing communication channels between early childhood (EC) educators and decision-makers, and the strategies of the improvement of language and literacy teachers’ professional development are also discussed.